What Influenced Early Secularization? A Statistical Analysis of the Results of the 1923 Referendum in Estonia. Issue 4 (19th July 2021) - Gortfelder, Mark
Abstract: In 1923, the first referendum of Estonia—one of the most secular countries in the world—was held. It came about as a public initiative to reinstate religious studies as a subject in public elementary schools after it had been banned by left‐dominated parliaments. The referendum underlined the schism between the political elite and the wider population regarding the societal role of religion, with only 28.8 percent of votes cast in opposition to the proposal. This article uses opposition to religious studies as a proxy for secularization, and asks which political, cultural, demographic, and economic factors influenced people to become secularized in an early phase of the process. The analysis is done using municipal‐level results of the referendum and standard linear, as well as two spatial models. It is shown that left‐wing political preference and male sex are the most important predictors of secularization.